Halichoerus grypus - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
11. Gray Seal Halichoerus grypus French: Phoque gris / German: Kegelrobbe / Spanish: Foca gris Other common names: Atlantic Seal, Horsehead Taxonomy. Phoca grypus Fabricius, 1791. No type locality given. Listed by V. B. Scheffer in 1958 as “Greenland.” There are three populations isolated geographically. Some authors recognized two subspecies (grypus in the western Atlantic Ocean and macrorhynchus in the eastern Atlantic Ocean), and the Baltic population was formerly referred to as the subspecies baltica; none of them are recognized here. Monotypic. Distribution. N Atlantic in subarctic to temperate waters, from S Labrador to Gulf of Maine, including Gulf of Saint Lawrence in NE North America, also in Iceland, Faroe Is, Norway, NW Russia, Baltic Sea, British Is, and North Sea and Atlantic coasts S to NW France (Brittany). Descriptive notes. Total length 195-230 cm (males) and 165-200 cm (females); weight 170-310 kg (males) and 100-190 kg (females). Newborns are 90-110 cm in length and weigh 11-20 kg. Gray Seals in the western Atlantic Ocean are significantly larger (males more than 400 kg and females more than 250 kg) than those in the eastern Atlantic Ocean. Adult Gray Seals are sexually dimorphic in body size and shape of heads and necks. Chests, necks, and shoulders of adult males are more massive than those of adult females, with many folds and wrinkles in skin and are heavily scarred from battles with other males during the breeding season. Nose of adult males is also longer and broader than that of adult females. Color of pelage varies substantially from black to brown to dark gray and even pale white, with darker blotches scattered dorsally and laterally and some ventrally. Adult females are generally lighter colored than males. Neonates have a silky white or yellow lanugo (fine,soft hair) that is molted at 2-3 weeks old into a lighter phase of the adult pelage. Habitat. Coastal areas of the northern North Atlantic Ocean and Baltic Sea. Breeding rookeries of Gray Seals are on rocky coasts and sandy ...